2018
DOI: 10.1111/odi.13008
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis investigation of miR‐199‐5p in oral submucous fibrosis based on bioinformatics analysis

Abstract: Objectives Fibrosis diseases are one of the leading causes of suffering and death. However, no systematic investigation has been carried out on fibrosis‐related genes. Materials and Methods By querying PubMed using keywords “fibrosis” and “gene” or “protein,” we identified fibrosis‐related genes in the last decade. Bioinformatics analysis was performed by MAS 3.0 software. Key miRNA was selected to assess its relationship with oral submucous fibrosis (OSF) and fibroblast functions. Results A total of 1,310 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Previous studies have demonstrated that mirna dysregulation is involved in cell proliferation, invasion and tumor metastasis (36,37). Yuan et al (38) reported that elevated mir-199a-5p promoted the apoptosis and suppressed the proliferation in oral submucous fibrocytes, which was consistent with the results of the present study indicating cell proliferation inhibition. Furthermore, a previous study reported that upregulated mir-199a-5p expression alleviated sustained endoplasmic reticulum stress, and thus protected hepatocytes from bile acid-induced cell death (18).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that mirna dysregulation is involved in cell proliferation, invasion and tumor metastasis (36,37). Yuan et al (38) reported that elevated mir-199a-5p promoted the apoptosis and suppressed the proliferation in oral submucous fibrocytes, which was consistent with the results of the present study indicating cell proliferation inhibition. Furthermore, a previous study reported that upregulated mir-199a-5p expression alleviated sustained endoplasmic reticulum stress, and thus protected hepatocytes from bile acid-induced cell death (18).…”
Section: Discussionsupporting
confidence: 92%
“…High levels of expression of mir199 are related to bleomycin-induced lung fibrosis in sheep and murine models and myofibroblast differentiation in oral submucous fibrosis with an increment of COL1A1 and COL3A1 (Yuan et al. 2019 ; Perera et al. 2021 ), and dysregulation of mir433 results in inhibition of AZIN1, a regulator of ECM production, with subsequent amplification of the TGFβ-1 signaling pathway (Li et al.…”
Section: Discussionmentioning
confidence: 99%